2022
DOI: 10.3892/mmr.2022.12742
|View full text |Cite
|
Sign up to set email alerts
|

Functional bowel symptoms in the general population (Review)

Abstract: Several patients with irritable bowel syndrome (IBS) do not seek medical attention for their symptoms. When patients with IBS seek help, the majority of them are handled at primary healthcare centers, whereas research studies are performed at tertiary healthcare centers. The present study aimed to summarize findings from >4,000 participants of the general population included in the Malmö Offspring Study (inclusion rate 46.7%). The participants were clinically examined, their blood and fecal samples collected, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…The lack of association of zonulin with gastrointestinal symptoms and IBD shows difficulty in selecting individuals with increased intestinal permeability based on the medical history and clinical symptoms. Similar results have already been reported in other studies [ 38 , 39 ]. It is likely that the relationship of IBD and gastrointestinal with biological treatment failure did not depend only on a damaged intestinal barrier.…”
Section: Discussionsupporting
confidence: 93%
“…The lack of association of zonulin with gastrointestinal symptoms and IBD shows difficulty in selecting individuals with increased intestinal permeability based on the medical history and clinical symptoms. Similar results have already been reported in other studies [ 38 , 39 ]. It is likely that the relationship of IBD and gastrointestinal with biological treatment failure did not depend only on a damaged intestinal barrier.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, parallels can be drawn between the phenotype of K8 flox/flox ;Villin-CreER t2 mice, and various diarrheic diseases other than IBD, such as microscopic colitis (54), leaky gut, viral and bacterial diarrhea. Similarities include constant, but not life threatening, diarrhea, modest neutrophil activity, and minor focal changes in crypt histomorphometry (55)(56)(57)(58). Not much is known about the possible keratin changes in diarrhea, microscopic colitis, irritable bowel syndrome, or colon functionality in general.…”
Section: Discussionmentioning
confidence: 99%
“…Our results did not align with previous findings regarding the protective effect of Blautia in human diseases. However, higher abundance of Blautia was also reported in the fecal microbiota of patients with irritable bowel syndrome, ulcerative colitis, functional gastrointestinal symptoms (Rajilić-Stojanović et al, 2011;Nishino et al, 2018;Ohlsson, 2022), and breast cancer (Luu et al, 2017), suggested its association to the local or systemic inflammation. Indeed, Blautia, especially Blautia coccoides, activates the secretion of inflammatory cytokines such as tumor necrosis factor α (TNF-α) to an even greater extent than lipopolysaccharide (Tuovinen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%